'Two decades after the war' - the management of international commons - Manuel Coelho (European Regional Science Association (ERSA), 2015)
Memory is important, also for Economics. The ephemeris can be used not only as moments of who relives the past in a single-rewind-perspective but of those who use these occasions to reflect on the past and to project the future from it. 1995 was a special year for fisheries in Portugal. Never before and never again, was the sector so under the eye of the media. First pages every day journals, opening in the TV daily informative programs?, and that, for more than three months. A unique scenario... The cause was a fish war in the NAFO area, between Spain and Canada, about a species, the turbot, that put also the Portuguese in a big tension. Two decades after the war, our proposal goes through resume the so-called turbot war and, from it, to reflect on its causes, how the problems were solved and to outlook for the guidelines of future research. Our paper therefore has the following structure. In the first and second points, the original problems of High Sea fisheries management and how they reflected in practice in the turbot war, are presented. In section 3 we reflect on how the problem was solved. Theoretically we shortly review the basic results of the literature on this issue, in particular those arising from the usual combination of the basic model of fisheries management with Game Theory. In empirical terms we draw attention to the diplomatic efforts between the EU and Canada to overcome disagreements that led to war and to promote a cooperative agreement that would avoid the problem of overfishing on the High Sea. The rationale and substance of the 1995 UN Agreement on Transboundary Resources and Highly Migratory Species, its strengths and weaknesses, is presented and discussed. Finally, in Section 4, the paper reflects on the theoretical and practical issues that still pose important questions to this problematic and ask for some perspectives on future developments.
Keywords: K00; Q00; 330; turbot war; hgh sea; management